Mga paraan ko ng pagsulat sa komiks - Villagracia, Bobby V. 1958-; University of the Philippines Press (Quezon City University of the Philippines Press, 2019)
On how to write comic strips.
In Tagalog.
Keywords: Cartooning -- Technique; Comic books, strips, etc -- Authorship; Graphic novels -- Authorship